Cocycle Perturbation on Banach Algebras (Communications in Mathematical Research, 2021)
Let $α$ be a flow on a Banach algebra $\mathcal{B}$, and $t → u_t$ a continuous functionfrom $\boldsymbol{R}$ into the group of invertible elements of $\mathcal{B}$ such that $u_sα_s(u_t) = u_{s+t}, s, t ∈ \boldsymbol{R}$.Then $β_t$ = Ad$u_t ◦ α_t$, $t ∈ \boldsymbol{R}$ is also a flow on $\mathcal{B}$, where Ad$u_t(B) \triangleq u_tBu^{−1}_t$ for any $B ∈ \mathcal{B}$. $β$ is said to be a cocycle perturbation of $α$. We show that if $α$, $β$ are twoflows on a nest algebra (or quasi-triangular algebra), then $β$ is a cocycle perturbationof $α$. And the flows on a nest algebra (or quasi-triangular algebra) are all uniformlycontinuous.